Volume Difference Inequalities for the Polars of Mixed Complex Projection Bodies (Communications in Mathematical Research, 2019)
In this paper, based on the notion of mixed complex projection and generalized the recent works of other authors, we obtain some volume difference inequalities containing Brunn-Minkowski type inequality, Minkowski type inequality and Aleksandrov-Fenchel inequality for the polars of mixed complex projection bodies.
Keywords: mixed complex projection body; polar; volume difference; Brunn-Minkowski type inequality; Minkowski type inequality